Trastorno de ansiedad generalizada y su repercusión en las relaciones interpersonales en un paciente de 17 años - Moran Rodriguez, Geanella Alexandra (2019)
The case study, it was carried out with the objective of demonstrating the generalized anxiety disorder and its impact on interpersonal relationships in a 17-year-old patient. For this, theoretical and bibliographic investigations were used, which help us to address the variables such as: generalized anxiety disorder and interpersonal relationships, which are immersed in the exposed theme, with the help of some techniques and the respective therapeutic plan from A systemic approach was achieved to obtain the expected results helping the patient to improve their quality of life, their social and family environment